How to build up a credible reputation regarding EY's actual sustainability engagement and corporate responsibility through responsible communication? - Koerner, Riccarda (2014)
In times of constant change, dynamic development and increasing expectations corporations are required to adapt stay flexible and follow the current development. Progressively, corporations engage not only with economic aspects but also with societal and ecological issues. EY Germany, formerly Ernst & Young GmbH, aligned its CSR-engagement with its corporate strategy. However, engaging in it is not enough. Corporations need to communicate about it in a responsible way to generate a win-win for society and the company itself. Thus, EY issued the research how to achieve positive impact on EY’s reputation and brand equity by aligning responsible CSR-communication with a dynamic CSR-engagement. CSR-communication faces the problem of being constantly confronted with potential green-washing reproaches and negative claims. Therefore, CSR-communication requires strategic management to enable selecting appropriate instruments, measures and tools to fulfil the intended purpose. Each communication instrument, channel or tool results in different outcomes and should be selected based on the purpose and the intended result. Clearly determined goals and sub-goals allow deriving the instruments logically which supports an adequate and effective communication strategy. Further, by developing the communication strategy step-by-step a following evaluation can be used to find the adjusting screws for improving specific aspects of the strategy itself. Yet, as EY‘s current focus lies on communicating and making CSR tangible internally, an implementation plan for the CSR-engagement itself has been developed to support the desired change of image and reputation with evidence and action. This way, EY proves its CSR-engagement with activities and overcomes the risk of green-washing reproaches.